AB0351 Differential perception about the csdmards on drug-induced interstitial lung disease between rheumatologists and non-rheumatologists. (12th June 2018) - Kobayashi, H.; Okubo, T.; Oka, H.; Aoki, A.
Abstract : Background: As disease modified anti-rheumatic-drugs (DMARDs) were the mainstay in the treatment of rheumatoid arthritis (RA), the opportunity for general physicians to also prescribe DMARDs has recently increased in Japan. After DMARDs were initiated by specialists, subsequent drug prescription by general physicians during remission should be expected 1 . However, general physicians are more likely than rheumatologists to feel it difficult to accept patients taking even conventional synthetics (cs) DMARDs but not biologics and such discomforts may be potential barriers to cooperative management between specialists and general physicians 2 . One of the reasons is because some csDMARDs such as methotrexate and leflunomide may induce pneumonitis or worsen RA-related pre-existing interstitial lung disease (ILD) as a rare but severe adverse event 3) . To minimise the risk, rheumatologists may choose low-risk csDMARDs smartly when the patients are concomitant with risk factors on ILD. Objectives: To measure the physicians' perspective toward the risk of each csDMARDs on drug-induced ILD and their attitude in prescribing the csDMARDs to a pre-existing ILD case. Methods: A questionnaire was given in an internet survey to registered physicians who take care of more than ten patients with RA in Japan. Topics covered were i) how is the risk of each csDMARD for drug-induced lung injury compared to methotrexate, ii) which csDMARDs should be applied to a case with mild pneumonitis on the chest CT. Cross tabulation analysis and χ 2 test as a statistical analysis was performed. Results: A total 184 physicians consisting of 66 rheumatologists (36%) and 118 non-rheumatologists (64%) responded. The physicians' mean age was 45 years old. The rheumatologists tended to belong to rheumatology and take care of more than 200 RA patients per month in university hospitals. On the other hand, the non-rheumatologists tended to belong to general medicine and manage less than 50 patients per month in their clinics. The csDMARDs except for methotrexate were more significantly prescribed by the rheumatologists. All rheumatologists but 24% of non-rheumatologists had managed RA patients with exacerbated ILD. On physicians' perspective toward the risk of each csDMARD, the rheumatologists considered that LEF was equal to or higher than MTX and that cyclosporine A (CyA), tacrolimus (TAC), salazosulfapyridine (SASP) was relatively safer (Figure A.). In cases with pre-existing ILD, more rheumatologists agreed to use the csDMARDs except for methotrexate and leflunomide. (Figure B.) R: rheumatologists, non-R: non-rheumatologists, MTX: methotrexate, LEF: leflunomide, CyA: cyclosporine A, TAC: tacrolimus, SASP: salazosulfapyridine, BUC: bucillamine, IGU: iguratimod Conclusions: We can find the gap of risk perception about each csDMARDs between rheumatologists and non-rheumatologist and the difference of attitude in prescribing to patients concomitant with risk factors. Considerable consensus and additional enlightenment to general physicians should be necessary. References: [1] Puchner R. Interface Management between General Practitioners and Rheumatologists-Results of a Survey Defining a Concept for Future Joint Recommendations. PLoS One2016Jan 7;11(1). [2] Garneau KL. Primary care physicians' perspectives towards managing rheumatoid arthritis: room for improvement. Arthritis Res Ther. 2011;13(6). [3] Roubille C. Interstitial lung diseases induced or exacerbated by DMARDS and biologic agents in rheumatoid arthritis: a systematic literature review. Semin Arthritis Rheum2014Apr;43(5). Disclosure of Interest: None declared